Justification of sorption composite usage on the basis of nanodisperse silica for sepsis prevention in complex treatment of purulent-inflammatory processes - O. A. Viltsaniuk; P. V. Belyaev; T. P. Osolodchenko; O. O. Viltsaniuk (Сучасні медичні технології, 2019)
Introduction. The problem of purulentinflammatory processes treatment and the prevention of sepsis remains one of the most pressing problems of surgery.